Explantation Rates and Healthcare Resource Utilization in Spinal Cord Stimulation. Issue 4 (15th February 2017) - Han, Jing L.; Murphy, Kelly R.; Hussaini, Syed Mohammed Qasim; Yang, Siyun; Parente, Beth; Xie, Jichun; Pagadala, Promila; Lad, Shivanand P.
Abstract : Objectives: Certain patients ultimately undergo explantation of their spinal cord stimulation (SCS) devices. Understanding the predictors and rates of SCS explantation has important implications for healthcare resource utilization (HCRU) and pain management. The present study identifies explant predictors and discerns differences in HCRU for at‐risk populations. Methods: We designed a large, retrospective analysis using the Truven MarketScan Database. We included all adult patients who underwent a SCS trial from 2007 to 2012. Patients were grouped into cohorts that remained explant‐free or underwent explantation over a three‐year period, and multivariate models evaluated differences in healthcare resource utilization. Results: A total of 8727 unique instances of trial implants between 2007 and 2012 were identified. Overall, 805 (9.2%) patients underwent device explantation. One year prior to SCS implantation, the explant cohort had significantly higher median baseline costs ($42, 140.3 explant vs. $27, 821.7 in non‐explant groups; p  < 0.0001), total number of pain encounters (180 vs. 103 p  < 0.0001), and associated costs ($15, 446.9 vs. $9, 227.9; p  < 0.0001). The explant cohort demonstrated increased use of procedures (19.0 vs. 9.0; p  < 0.0001) compared to non‐explanted patients. For each month after initial SCS implantation, explanted patients had a slower decrease in total costs (4% vs. 6% in non‐explant; p  < 0.01). At the month of explant, explant patients were expected to have incurred 2.65 times the total cost compared to the non‐explant cohort (CR 2.65, 95% CI [1.83, 3.84]; p  < 0.001). Medium volume providers had lower rates of explantation at one‐year and three‐years compared to low volume providers ( p  = 0.042). Increased age and Charlson index were independent predictors of explantation during the same periods. Conclusions: In this nationwide analysis, we identified that SCS device explantation is correlated with patients who have higher baseline costs, higher total cost post‐SCS implantation, and increased use of procedures to control pain. The higher rates of explantation at three‐years postimplant among low volume providers suggest that variations in provider experience and approach also contributes to differences in explantation rates.